Pemanfaatan Speech Recognition Berbasis Sound Type Artificial Intelligence untuk Menulis Ayat Al-Qur'an Surah Al-A’la (87): 14–19 - Jasiah, Jasiah; Winda, Winda; Mahrita, Mahrita; Ningsih, Eka Dwi (Lembaga Yasin AlSys, 2025)
The growing use of speech recognition technology in Qur’anic learning and the significant role of artificial intelligence in enhancing educational quality at madrasahs form the background of this study. The aim is to explore the utilization of speech recognition based on sound type artificial intelligence to assist students in writing verses from Surah Al-A‘la (87): 14–19. This study adopts a qualitative approach with a sample of 16 eighth-grade students. Data were collected through interviews, observations, and documentation, and analyzed descriptively. The findings reveal that the use of sound type AI technology enhances students’ accuracy and confidence in writing Qur’anic verses. These results align with technology-based learning theories that support the integration of digital tools in religious education. The study concludes that speech recognition technology serves as an effective aid in Qur’anic learning. Its implications include enriching the literature on educational technology and encouraging madrasahs to integrate digital innovations into the learning process. Furthermore, this study opens avenues for further exploration of similar technologies across diverse educational contexts.